2021
DOI: 10.3390/foods10112734
|View full text |Cite
|
Sign up to set email alerts
|

Rosemary Essential Oils as a Promising Source of Bioactive Compounds: Chemical Composition, Thermal Properties, Biological Activity, and Gastronomical Perspectives

Abstract: Rosemary (Rosmarinus officinalis L.) is a plant worldwide cultivated mainly for essential oils, extracts, and as a spice. Up-to-date results showed diversity in composition of the essential oils, which may influence their quality, biological activity, and thermal properties. Therefore, the aim of this study was to investigate the chemical composition, antimicrobial activity, and thermal properties of the rosemary essential oils originating from Serbia and Russia. Additionally, oils were added to the sunflower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Chemical profile of EO samples was done by using Thermo Fisher Focus GC coupled with Polaris Q mass spectrometer according to the previously reported ( Šojić et al, 2019 ) and fully described method ( Micić et al, 2021 ). Dissolved samples were injected into the GC through TriPlus autosampler (2 µL) into the TR WAX-MS column (30 m × 0.25 mm, 0.25 µm).…”
Section: Methodsmentioning
confidence: 99%
“…Chemical profile of EO samples was done by using Thermo Fisher Focus GC coupled with Polaris Q mass spectrometer according to the previously reported ( Šojić et al, 2019 ) and fully described method ( Micić et al, 2021 ). Dissolved samples were injected into the GC through TriPlus autosampler (2 µL) into the TR WAX-MS column (30 m × 0.25 mm, 0.25 µm).…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of antimicrobial activity of the DMEO and DMH was completed by the disk-diffusion method. As Micić et al [ 76 ] reported in detail, the nutrient medium (Müller–Hinton agar or Sobouraud maltose agar) was inoculated with microbial suspensions (approx. 6 log CFU/mL) and the samples (15 μL) were applied onto three sterile cellulose discs.…”
Section: Methodsmentioning
confidence: 99%
“…As a preliminary step in a screening of the antimicrobial potential of different S. montana extracts, the disc-diffusion method was chosen and completely performed as described by Micić et al [ 73 ]. The most important parts of the described method imply the usage of the freshly prepared suspensions of overnight cultures for the inoculation of adequate nutrient medium in a Petri dish and the application of the tested extracts (15 μL) onto three sterile discs for each microorganism previously applied on the medium.…”
Section: Methodsmentioning
confidence: 99%
“…The minimal inhibitory concentration was determined for the microorganisms that were sensitive to the initial concentration of the extract. Different decreasing concentrations of the extract were tested (100–0.78%) using the microdilution method, which was previously described by Micić et al [ 73 ]. The MIC value was determined using Equation (1), involving a number of microorganisms in the positive control for microbial growth ( N c ) and treated sample ( N t ).…”
Section: Methodsmentioning
confidence: 99%